Migrant Children’s Experiences of Learning English as an Additional Language in Irish Primary Schools. - Whittaker, Chelsea (Trinity College (Dublin, Ireland). School of Education, 2019)
This study aimed to investigate migrant learners’ experiences of learning English as an Additional Language (EAL) in Irish primary schools, within the context of the school community and the larger language-in-education policy framework in Ireland. Census data indicates that since the 1990s, Ireland has experienced significant inward migration (Central Statistics Office, 2018). This has resulted in an influx of immigrants from a wide variety of origins and thus increased ethnic diversity (Devine, 2005; Devine, Kenny, & Macneela, 2008). The Official Languages Act of 2003 lists Irish and English as the official languages of the Republic of Ireland, however, data reveals that in 2016, 612,018 residents spoke a language other than Irish or English at home (Central Statistics Office, 2016). This number shows an increase of 19.1% on the 2011 figures (Central Statistics Office, 2016). As a result, meeting the needs of increasing numbers of minority ethnic and linguistic identities in Irish schools has become more urgent (Devine, Kenny, & Macneela, 2008; Nowlan, 2008; Faas, Smith, & Darmody, 2018). A challenge facing schools is the teaching of English, and in some cases Irish, as an additional language to migrant learners (Mahon, 2017). The aims of this research translated into the following overarching research question: “What are migrant children’s experiences of learning English as an additional language in Irish primary schools?”. This study comprised of a qualitative, dual case-study featuring two English-medium, senior primary schools within the Greater Dublin Area. Data collection included linguistic landscaping (LL), an online teacher survey and group interviews with EAL learners. Braun and Clarke’s (2006, 2013) Thematic Analysis (TA) was utilised to analyse the data. Themes generated from the data were analysed in the context of both schools and also related back to language-in-education policies in Ireland and the broader socio-political context. Results indicated that English significantly dominates over Irish, ISL, Irish Traveller Cant and migrant languages. Furthermore, despite the intentions of policy, de facto subtractive bi/multilingualism was evidenced and a deficit ideology regarding bi/multilingualism pervaded in both cases. An isolated enthusiasm towards cultural and linguistic diversity was present and both teachers and learners indicated a lack of support and material resources in relation to EAL teaching and learning. Additionally, the data indicates a clear need for a comprehensive, national, language-in-education policy that embraces heteroglossic ideologies and a ‘language-as-resource’ orientation towards language teaching in Ireland. Keywords: EAL, language, education, diversity, migration, Ireland.
Keywords: Education; Language Education